2016
DOI: 10.1016/j.nlm.2016.07.009
|View full text |Cite
|
Sign up to set email alerts
|

The role of working memory and declarative memory in trace conditioning

Abstract: Translational assays of cognition that are similarly implemented in both lower and higher-order species, such as rodents and primates, provide a means to reconcile preclinical modeling of psychiatric neuropathology and clinical research. To this end, Pavlovian conditioning has provided a useful tool for investigating cognitive processes in both lab animal models and humans. This review focuses on trace conditioning, a form of Pavlovian conditioning typified by the insertion of a temporal gap (i.e., trace inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 250 publications
(376 reference statements)
1
38
0
Order By: Relevance
“…Thus, deficits described here are likely not due to altered fear learning or expression, but rather alterations in complex learning. Moreover, considering that delay fear conditioning is hippocampus and PFC independent (Morgan et al, 1993; Phillips and LeDoux, 1992), our data suggests that adolescent exposure to chronic nicotine can elicit long-term deficits in cued forms of learning that engage forebrain-dependent processes, i.e., trace conditioning (Connor and Gould, 2016; Kim and Jung, 2006). Furthermore, considering that trace conditioning recruits working memory-like processes, our data also fits well with work indicating that adolescent, but not adult, chronic nicotine exposure results in long-term deficits in visuospatial attention, an PFC-dependent task (Counotte et al, 2008).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Thus, deficits described here are likely not due to altered fear learning or expression, but rather alterations in complex learning. Moreover, considering that delay fear conditioning is hippocampus and PFC independent (Morgan et al, 1993; Phillips and LeDoux, 1992), our data suggests that adolescent exposure to chronic nicotine can elicit long-term deficits in cued forms of learning that engage forebrain-dependent processes, i.e., trace conditioning (Connor and Gould, 2016; Kim and Jung, 2006). Furthermore, considering that trace conditioning recruits working memory-like processes, our data also fits well with work indicating that adolescent, but not adult, chronic nicotine exposure results in long-term deficits in visuospatial attention, an PFC-dependent task (Counotte et al, 2008).…”
Section: Discussionmentioning
confidence: 89%
“…Thus, we decided to examine the effects of prior chronic nicotine exposure on trace fear conditioning, which like delay conditioning also depends on forming a discrete CS-US association. However, unlike delay conditioning in which the CS and US temporally overlap, the CS and US in trace conditioning are temporally separated making the task hippocampus and PFC-dependent and may model aspects of working and declarative memory (Connor and Gould, 2016). Moreover, the PFC and hippocampus undergo maturation during adolescence (Gogtay et al, 2004) and have previously been shown to be altered by adolescent nicotine exposure (Goriounova and Mansvelder, 2012; Holliday et al, 2016; Portugal et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, manipulations of the mPFC have been found to disrupt some forms of cue discrimination (Meyer and Bucci, 2014; Sangha et al, 2014) and conditioned inhibition (Rhodes and Killcross, 2007), and individuals with PTSD have altered prefrontal cortical and hippocampal activity (Rauch et al, 2006; Shin et al, 2004, 2006). Finally, learning trace associations is dependent on the mPFC and hippocampus (Connor and Gould, 2016; Gilmartin and Helmstetter, 2010; Gilmartin et al, 2013b; Misane et al, 2005; Raybuck and Gould, 2010). Therefore, we investigated the effect of nicotine administered directly into the dorsal hippocampus, ventral hippocampus, and prelimbic cortex on backward trace conditioned safety.…”
Section: Introductionmentioning
confidence: 99%
“…2A). This type of task, implying a delay between the CS offset and the US onset (here, 1 s), is then a trace-conditioning task, that differs from a delay-conditioning task where the CS and US overlap (Connor and Gould, 2016).…”
Section: Methods: Computational Model and Simulated Behavioral Tasksmentioning
confidence: 99%
“…For the last two decades, a great amount of experimental studies depicted which brain areas send this information to the VTA. Notably, a subpopulation of pedunculopontine tegmental nucleus (PPTg) has been found to send the actual reward signal to dopamine neurons (Kobayashi and Okada, 2007; Okada et al, 2009; Keiflin and Janak, 2015), while other studies showed that the prefrontal cortex (PFC) and the nucleus accumbens (NAc) respond to the predictive cue (Keiflin and Janak, 2015; Oyama et al, 2015; Funahashi, 2006; Connor and Gould, 2016; Le Merre et al, 2018), highly depending on VTA DA feedback projections in the PFC (Puig et al, 2014; Popescu et al, 2016) and the NAc (Yagishita et al, 2014; Keiflin and Janak, 2015; Fisher et al, 2017). However, how each of these signals are integrated by VTA DA neurons during classical-conditioning remains elusive.…”
Section: Introductionmentioning
confidence: 99%